Using gamification in accounting education: a systematic literature review (2017 – 2023) - Almuntsr, Nowara. M.; Muhamad, Haslinah; San, Ong Tze; Mohammed Shah, Sabarina (Human Resources Management Academic Research Society (HRMARS), 2024)
Gamification is a tool often used to improve the teaching-learning process. Given the importance of the topic in academic filed, this article presents a systematic review of the articles that are published in accounting education journals on this topic. The main objective of this article is, to examine previous work in the field of gamification. An analysis of the literature covering 17 articles available in the Web of Science and Scopus databases “Between 2017 to 2023” were conducted, to determine and shape the main themes and concepts proposed in these articles on gamification. The analysis is performed by answering the research question, “What is the effect of using gamification on accounting education, and what is the possibility of its use in teaching-learning process?". The main result of this study shows that, there is a positive effect of using gamification in accounting education is predominant in the results of most studies. While it is not possible to ignore some of the negative effects of this topic. In additional, concern must be taken to ensure the availability of all requirements for the use of this approach in accounting education to universities, lecturers and students in order for its use to be meaningful and feasible. Furthermore, a lot of work is still required in making gamification possible in accounting education due to the various limitations mentioned in the previous studies.